2007
DOI: 10.4049/jimmunol.179.8.5433
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Vacuolating Cytotoxin Inhibits Activation-Induced Proliferation of Human T and B Lymphocyte Subsets

Abstract: Helicobacter pylori are Gram-negative bacteria that persistently colonize the human gastric mucosa despite the recruitment of immune cells. The H. pylori vacuolating cytotoxin (VacA) recently has been shown to inhibit stimulation-induced proliferation of primary human CD4+ T cells. In this study, we investigated effects of VacA on the proliferation of various other types of primary human immune cells. Intoxication of PBMC with VacA inhibited the stimulation-induced proliferation of CD4+ T cells, CD8+ T cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 41 publications
1
78
0
Order By: Relevance
“…In addition, VacA suppressed IL-2-induced cell cycle progression without affecting IL-2-dependent survival (Sundrud et al 2004). Furthermore, Torres et al (2007) reported that VacA inhibited the proliferation of CD8+ T cells and B cells. VacA inhibited both T-cell-induced and PMA/anti-IgM-induced proliferation of purified B cells.…”
Section: Other Disruptions Of Cellular Signal Transductionmentioning
confidence: 97%
“…In addition, VacA suppressed IL-2-induced cell cycle progression without affecting IL-2-dependent survival (Sundrud et al 2004). Furthermore, Torres et al (2007) reported that VacA inhibited the proliferation of CD8+ T cells and B cells. VacA inhibited both T-cell-induced and PMA/anti-IgM-induced proliferation of purified B cells.…”
Section: Other Disruptions Of Cellular Signal Transductionmentioning
confidence: 97%
“…This suggests that the role of the vacA allele could differentially affect disease progression based on other virulence factors. This could be due to the finding that VacA acts as an immune modulator (16,52) and perhaps changes the immune response to the immunogenic CagA. Like CagA, VacA was found to disorganize the cytoskeleton of gastric epithelial cells, leading to increased cell spreading and growth (39).…”
Section: Vol 48 2010mentioning
confidence: 99%
“…VacA is another important toxin that is produced and secreted by all H. pylori strains (4,11) and was previously shown to have various modes of action (12,16,27,39,49,50,52,56). Like CagA, VacA has been shown to contain a number of polymorphisms.…”
mentioning
confidence: 99%
“…VacA causes multiple alterations in gastric epithelial cells, including swelling of endosomes (vacuolation) (11,12), permeabilization of mitochondrial membranes, and activation of mitogen-activated protein kinases (4,(7)(8)(9). In addition to its effects on gastric epithelial cells, VacA can disrupt the functions of many types of immune cells (T cells, B cells, neutrophils, eosinophils, and monocytes) (4,(7)(8)(9)(13)(14)(15)(16). The cellular activities of VacA are attributed mainly to its ability to form anion-selective channels in host cells (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%